PENGARUH KARAKTERISTIK PETANI TERHADAP EFEKTIVITAS KOMUNIKASI PENYULUH PERTANIAN PADA PENGGUNAAN BENIH PADI UNGGUL DI KABUPATEN KUBURAYA - asti, asti; Kucan, Benedictus; Ellyta, Ellyta (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
The use of superior rice seeds is one of the strategic efforts to enhance productivity and food security. The effectiveness of extension communication plays a crucial role in the adoption of this technology at the farmer level. This study employed a numerical rating scale and multiple linear regression analysis. The results showed that extension communication in Kuburaya District was fairly effective, with an average score of 61.55. The majority of farmers were aged between 15 and 65 years, had elementary-level education, 20–35 years of farming experience, and an average land size of 0.5 to less than 1 hectare. The multiple linear regression analysis indicated that the variables of age (X1), formal education (X2), farming experience (X3), and land size (X4) simultaneously had a significant effect on the effectiveness of agricultural extension communication (Y).